Probing Benchmark Models of Hidden-Sector Dark Matter with DAMIC-M - Aggarwal, K. (2025)
We report on a search for sub-GeV dark matter (DM) particles interacting with electrons using the DAMIC-M prototype detector at the Modane Underground Laboratory. The data feature a significantly lower detector single − rate (factor 50) compared to our previous search, while also accumulating a 10 times larger exposure of ∼1.3  kg−day. DM interactions in the skipper charge-coupled devices (CCDs) are searched for as groups of two or three adjacent pixels with a total charge between 2 and 4  −. We find 144 candidates of 2  − and 1 candidate of 4  −, where 141.5 and 0.071, respectively, are expected from background. With no evidence of a DM signal, we place stringent constraints on DM particles with masses between 1 and 1000  MeV/2 interacting with electrons through an ultralight or heavy mediator. For large ranges of DM masses below 1  GeV/2, we exclude theoretically motivated benchmark scenarios where hidden-sector particles are produced as a major component of DM in the Universe through the freeze-in or freeze-out mechanisms.